Time and reason of exit of minors from a refugee centre: the role of family links - Manuela Stranges; François-Charles Wolff (Genus)
Abstract This paper investigates the duration of stay and reason of exit from a reception centre among young migrants arriving in Italy by sea, drawing on unique data from a centre for refugees and asylum seekers located in the southern region of Calabria, covering a 10-year period (1 January 2009–31 December 2018). The analysis focuses on the role of family status at entry in shaping both length of stay and exit pathways. Results show that minors entering with family members stay nearly five times longer than those arriving alone. Over half of the minors leave the centre voluntarily, while about a quarter are transferred elsewhere. Substantial variation by country of origin emerges for both the length of stay and the reason of exit. Multivariate analyses confirm that family status strongly influences both outcomes, even after controlling for individual-level covariates.